The Influence of Self Efficacy, Competence, and Training on Work Readiness (Study on MSIB Management Study Program UPN "Veteran" East Java Students) - Lala Dinda Pratiwi; Hesty Prima Rini (International Journal of Economics (IJEC), 2023)
The abilities required to compete in the workplace are changing as a result of the expanding nature of the labor market. Therefore, it is required of college graduates to be self-assured, skilled, and fully competent within themselves to support work preparedness. The purpose of this study is to understand the effects of self-efficacy, competence, and training on the degree to which MSIB students enrolled in the UPN "Veteran" East Java Management study program are prepared for the workforce. This study uses quantitative descriptive methods. 45 students in their last year of the Management Study Program who had successfully completed the MSIB program made up the study's population. Total sampling was the method utilized in this study. In this study, 45 students served as samples. The Partial Least Square (PLS) program is used in this work as an analysis tool. The study's findings demonstrated that for MSIB students enrolled in the Management study program at the "Veteran" National Development University, East Java, self-efficacy and competence had a favorable and significant impact on work preparedness, whereas training had no such impact.